Hemoglobin Mississippi (beta 44ser----cys). Studies of the thalassemic phenotype in a mixed heterozygote with beta +-thalassemia. - Steinberg, M H (1987)
Hemoglobin Mississippi (HbMS: beta 44ser----cys) has anomalous properties that include disulfide linkages with normal beta-, delta-, gamma-, and alpha-chains, and the formation of high molecular weight multimers. While heterozygotes for HbMS are clinically and hematologically normal and carriers of the beta +-thalassemia gene in our family had mild microcytic anemia, the proband with HbMS-beta +-thalassemia had a hemoglobin level of 7 g/dl, mean corpuscular volume (MCV) of 68 fl, reticulocytes of 2-6%, HbF of 18%, marked anisocytosis and poikilocytosis, and splenomegaly, all features of thalassemia intermedia. With oxidant stress, her erythrocytes developed multiple dispersed Heinz bodies, but HbMS was only mildly unstable. HbMS was susceptible to proteolytic degradation in the presence of ATP. The unexpectedly severe clinical findings in HbMS-beta +-thalassemia may result from the proteolytic digestion of HbMS, as well as the excessive alpha-chains characteristic of beta +-thalassemia, which combined provide the increment of cellular damage that results in the phenotype of thalassemia intermedia.